Deteksi Kecacingan pada Peternak Sapi dengan Metode Harada Mori dan Metode Stool di Sumenep Madura - Dwi Aprilia Anggraini; Norma Farizah Fahmi; Rizka Efi Mawli; Fajriatul Hasanah; Moh Saiful Hakiki (LPPM Universitas Abdurrab, 2025)
Intestinal nematodes are primarily transmitted through the soil. In the human body, the worms travel through the bloodstream to the heart, lungs, and throat, then are swallowed and enter the intestines. Severe worm infections can lead to malnutrition and impaired growth and development. The aim of this study was to determine the difference in effectiveness between the Harada Mori method and the stool method in measuring the association between STH infection and cattle breeders in Neggara Bungbungan Hamlet. The research method used was quantitative. This study was conducted at the Parasitology Laboratory of Noor Huda Mustofa University from April 5-19, 2025. The sample size was 25 respondents suspected of having worms, whose erythrocyte levels were then examined. Data were collected using a questionnaire and IBM SPSS 25, presented in tabular form, and then explained in narrative form. STH infection in the stool method was classified as high, with 23 eggs (92%) found, and in the Harada Mori method, 17 larvae (68%). The results of the marginal homogeneity statistical test obtained a p-value of 0.000 < 0.005. The relationship between STH infection in the stool method and eosinophil levels obtained a p-value of 0.016 < 0.005 using the Kruskal Wallis statistical test. There is a significant difference between the stool method and the Harada Mori method. There is a significant correlation between the stool method and eosinophil levels.